New Gulf Streams – Middle East and Eastern Africa Intersected: An introduction - Daniele, G.; Ramos, M.; Ylönen, A. (Cadernos de Estudos Africanos, 2022)
The present thematic issue of the Cadernos de Estudos Africanos contains a selection of papers presented at the 4th AEGIS Thematic Conference of the Collaborative Research Group Africa in the Indian Ocean (CRG-AIO). The conference, entitled New Gulf Streams Middle East and Eastern Africa Intersected, was organized by the Center for International Studies of the University Institute of Lisbon (CEI-IUL) during September 16-17, 2021, in partnership with AEGIS-AIO.